Mempersoalkan Kebenaran Bahasa Iklan dalam Media Massa : Tinjauan Kebenaran-Kebenaran secara Epistemologi (Jurnal Ilmu Pendidikan Keagamaan Kristen : Arastamar, 2025)
This article aims to question and critically examine the notion of truth within advertising language as disseminated through mass media, by employing an epistemological framework. In the current era of rapid information flow, advertising language tends to deliver messages that are persuasive and, at times, manipulative, thereby raising essential epistemic concerns regarding the extent to which such language conveys truth. The study adopts a qualitative approach through library research, involving the collection and analysis of written sources such as books, scholarly journals, and academic articles discussing theories of truth in epistemology—including coherence, correspondence, pragmatism, and consensus—alongside studies on advertising discourse and mass media. The primary focus lies in exploring how these epistemological theories can be applied to evaluate the truth-claims embedded in advertising language and to assess their influence on the public's knowledge construction and behavioral responses. The significance of this study is particularly relevant for families and young people, urging them to engage more critically and reflectively with advertising messages encountered in everyday life. In doing so, this article contributes to the development of epistemological awareness in relation to advertising language within the context of contemporary social life.